A sandwich-type electrochemical immunosensor based on multiple signal amplification for α-fetoprotein labeled by platinum hybrid multiwalled carbon nanotubes adhered copper oxide. (1st April 2015) - Jiang, Liping; Han, Jian; Li, Faying; Gao, Jian; Li, Yueyun; Dong, Yunhui; Wei, Qin
Abstract: In this work, we designed a novel and ultrasensitive sandwich-type electrochemical immunosensor for quantitative detection of α-fetoprotein (AFP), using β-cyclodextrin functionalized graphene (CD-GS) as the platform and platinum hybrid multiwalled carbon nanotubes adhered copper oxide (Pt@CuO-MWCNTs) as labels. CD-GS has high specific surface area, ideal dispersibility and good biocompatibility, which was used to efficiently capture more primary antibodies (Ab1 ). Pt, CuO and multiwalled carbon nanotubes (MWCNTs) can be used as catalysts for the decomposition of hydrogen peroxide. The Pt@CuO-MWCNTs realized multiple amplified signals due to their synergy. Therefore, Pt@CuO-MWCNTs was used as the marker, combined with secondary antibodies (Ab2 ) and this has the effect of multiple amplified signals to catalyze hydrogen peroxide. Under optimal conditions the designed immunosensor exhibited a wide linear range from 1 pg mL −1 to 20 ng mL −1 with a low detection limit of 0.33 pg mL −1 (S/N = 3) for AFP. The designed immunosensor showed good selectivity, reproducibility and stability, which could provide potential applications in clinical monitoring of AFP.